Groin Hernias in Women—A Review of the Literature - Köckerling, Ferdinand; Koch, Andreas; Lorenz, Ralph (Frontiers in Surgery, 2019)
Introduction To date, there are few studies and no systematic reviews focusing specifically on groin hernia in women. Most of the existing knowledge comes from registry data. This present systematic review now reports on such findings as are available on groin hernia in women. Material and Methods A systematic search of the available literature was performed in September 2018 using Medline, PubMed, Google Scholar, and the Cochrane Library. For the present analysis 77 publications were identified. Results The lifetime risk of developing a groin hernia in women is 3-5.8%. The proportion of women in the overall collective of operated groin hernias is 8.0–11.5%. In women the proportion of femoral hernias is 16.7-37%. Risk factors for development of a groin hernia in women are high age, positive family history and constipation. A groin hernia during pregnancy should not be operated on. The rate of emergency procedures in women, at 14.5-17.0%, is three- to fourfold higher than in men, and at 40.6% is even higher for femoral hernia. Therefore, watchful waiting is not indicated in women. During surgical repair of groin hernia in females the presence of a femoral hernia should always be excluded and if detected should be repaired using a laparo-endoscopic or open preperitoneal mesh technique. A higher rate of chronic postoperative inguinal pain must be expected in females. Conclusion Special characteristics must be taken into account for repair of groin hernia in women.